Tindak Tutur Representatif dalam Beberapa Versi Iklan Shopee Kampanye Tanggal Kembar Tahun 2025 - Bella Septia Amalia Kahfi; Aulia Destyana Maharani; Anisah Hapsari; Ananda Syinta Panca Rani; Ghadiva Luthfiyah Shalhiyah; Asep Purwo Yudi Utomo; Riri Kumalasari; Ahmad Mubarok (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2026)
Advances in digital technology have driven significant progress in e-commerce, which leverages language as a key marketing strategy, particularly through advertising. Shopee’s advertisements in various 2025 “twin-date” campaigns demonstrate the use of language that is not only informative but also persuasive through representative speech acts. This study aims to identify the types and explain the functions of representative speech acts in these advertisements. The method used is qualitative descriptive with a pragmatic approach. The data consists of utterances in Shopee advertising videos taken from the YouTube platform, collected through free-listening and note-taking techniques, and then analyzed using matching and categorization techniques. The results indicate the presence of 25 representative speech acts categorized into four groups: reporting, claiming, stating, and boasting, with a predominance in the reporting and claiming categories. These findings suggest that representative speech acts not only serve to convey information but also play a role in building trust, reinforcing promotional claims, and influencing consumer purchasing decisions. This study is expected to enrich pragmatic research and provide practical contributions to the effective use of language in digital advertising.